2015
DOI: 10.1017/s1431927615004705
|View full text |Cite
|
Sign up to set email alerts
|

Role of Interface Structure and Chemistry in Resistive Switching of NiO Nanocrystals on SrTiO3

Abstract: Nickel oxide (NiO) is a binary metal oxide that is found to have resistive switching (RS) properties, which makes it a viable candidate for next generation resistive random access memories (RRAMs). The demand for high-density memories has concentrated on RS materials with scalable dimensions. In these nanoscaled devices, the presence of point and line defects, composition inhomogeneity, and atomic interdiffusion interfaces have been shown to have a significant impact on properties.The objective of this study i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…17 Moreover, detailed transmission electron microscopy (TEM) and electron energy loss spectrum (EELS) studies have revealed that the oxygen vacancies are preferably located at the NiO/Nb:STO interface and might be modulated by the electric field. 32 Therefore, it should be expected that the oxygen vacancies at the edge of the nanocrystals can actively drive the switching performance.…”
mentioning
confidence: 99%
“…17 Moreover, detailed transmission electron microscopy (TEM) and electron energy loss spectrum (EELS) studies have revealed that the oxygen vacancies are preferably located at the NiO/Nb:STO interface and might be modulated by the electric field. 32 Therefore, it should be expected that the oxygen vacancies at the edge of the nanocrystals can actively drive the switching performance.…”
mentioning
confidence: 99%
“…45,46 In the case of NiO grown on STO substrate, we know previously that the surface of STO is reduced. 47 Through careful and highresolution electron energy loss spectra (EELS) analysis, we found that the interface has Ti with lower valence (+4−δ) than the stoichiometric value of +4, even for STO several layers away from the Ni−STO interface. Thus, during growth the NiO/STO interface is not fully chemically stoichiometric.…”
Section: Acs Applied Electronic Materialsmentioning
confidence: 93%
“…Thus, during growth the NiO/STO interface is not fully chemically stoichiometric. 47 According to the metal/metal oxide interface encapsulation/ decoration theory, it has been proposed that minimization of surface energy is one of the driving forces for encapsulation. 42 To have encapsulation, two conditions are necessary: (1) the surface energy of the nanoparticle is larger than that of the substrate, and (2) the work function of the nanoparticle is higher than that of the substrate.…”
Section: Acs Applied Electronic Materialsmentioning
confidence: 99%